The Effectiveness of Using Audio Visual Method to Enrich Students’ Vocabulary at Grade VII MTs Muhammadiyah 04 Sibolga - Huda, Rahmat; Herawati Parapat, Lili; Amri, Khairul; Noviantika, Mega; Husein, Nabilah (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This research aims to find out the effectiveness of the use of Audio-Visual method in enriching the vocabulary of students at grade VII MTs Muhammadiyah 04 Sibolga. The methods in this research are quantitative methods using pre-experimental designs as well as one group pretest and post-test. The subject of this research is a student of seventh grade who has only one class. The sample of this research involved 24 students. The instruments used in this research includepre-test, post-test and questionnaire. The results of this research show that the total pre-testaverage is 50,83 which is categorized as “poor”, while the post-test mean is 79,16 and is categorised as “good”. Based on data analysis, t-count values are higher than t-table values (11,737gt;2,012), meaning there is a significant difference. Therefore, H 0 is rejected and H 1 is accepted. The results of the questionnaire showed that the average percentage score of the questionnaire was 85.83% and was classified into the “very good” criteria. It shows that students positively responded to the Audio-Visual method. This research concludes that Audio-Visual method is effective to enrich students’ vocabulary.Keywords: Audio-Visual, Subtitled Video, Vocabulary